2018
DOI: 10.1111/1759-7714.12924
|View full text |Cite
|
Sign up to set email alerts
|

Application of endoscopic ultrasound‐guided‐fine needle aspiration combined with cyst fluid analysis for the diagnosis of mediastinal cystic lesions

Abstract: BackgroundMediastinal cystic lesions account for approximately 15–20% of all mediastinal masses and are difficult to differentiate because of similar imaging manifestation. The aim of this study was to differentiate mediastinum cystic lesions through endoscopic ultrasound‐guided‐fine needle aspiration (EUS‐FNA) and parameters from cyst‐fluid analysis.MethodsOver a period of eight years, 37 patients suspected with mediastinal cystic lesions were assessed. Cyst fluid was collected via EUS‐FNA and further examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Oesophageal cancer is often widely distributed in a region and concentrated to form a high incidence area, and there are also low incidence areas in the high incidence area, showing the relationship between geography and the occurrence of oesophageal cancer. The incidence level of oesophageal cancer varies widely among different regions and populations, with rural areas having a higher incidence than urban areas [ 1 ]. The aetiology of oesophageal cancer is still unclear, and with the development of epidemiology, it is found that the incidence of oesophageal cancer involves multiple factors, each of which can play different roles due to differences in their exposure opportunities and dose intake caused by differences in geography, customs, and lifestyle behavioural habits, and the main prevalence factors may vary from region to region [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oesophageal cancer is often widely distributed in a region and concentrated to form a high incidence area, and there are also low incidence areas in the high incidence area, showing the relationship between geography and the occurrence of oesophageal cancer. The incidence level of oesophageal cancer varies widely among different regions and populations, with rural areas having a higher incidence than urban areas [ 1 ]. The aetiology of oesophageal cancer is still unclear, and with the development of epidemiology, it is found that the incidence of oesophageal cancer involves multiple factors, each of which can play different roles due to differences in their exposure opportunities and dose intake caused by differences in geography, customs, and lifestyle behavioural habits, and the main prevalence factors may vary from region to region [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic ultrasound is a newer technology that can potentially aid in diagnosis of thymic cysts ( 56 - 58 ). As previously discussed, caution should be taken with endoscopic aspiration of cyst contents when diagnosis of thymic or mediastinal cyst is suspected, as analysis of fine needle aspiration is usually non-diagnostic 73% of the time, with risk of infection, sepsis, and death ( 41 , 42 , 50 , 58 ).…”
Section: Diagnosismentioning
confidence: 99%
“…Cystic masses of the mediastinum are heterogeneous groups of lesions, including congenital abnormalities, infections, and neoplasms and account for 15%–20% of all mediastinal masses. [ 27 ] The diagnosis of mediastinal cystic lesions is difficult as benign lesions can mimic cancer manifestations in CT or magnetic resonance imaging (MRI) evaluation. [ 28 ] Although available data are scarce, EUS-guided sampling seems to have tremendous diagnostic potential in the differentiation of those lesions.…”
Section: Clinical Implications Of Eus Mediastinal Examinationmentioning
confidence: 99%
“…described 37 patients who underwent EUS-FNA of mediastinal cystic lesions. [ 27 ] Cyst fluid was collected and further examined using cytological and biochemical techniques. Interestingly, the authors revealed that prior CT or MRI mistakenly distinguished eight cases as solid masses (27.03%), but EUS revealed cystic characteristics.…”
Section: Clinical Implications Of Eus Mediastinal Examinationmentioning
confidence: 99%